Response to a combination of oxygen and a hypnotic as treatment for obstructive sleep apnoea is predicted by a patient’s therapeutic CPAP requirement - Landry, Shane A. (Respirology, 2017)
BACKGROUND AND OBJECTIVE: Upper airway collapsibility predicts the response to several non-CPAP interventions for obstructive sleep apnoea (OSA). Measures of upper airway collapsibility cannot be easily performed in a clinical context; however, a patient’s therapeutic CPAP requirement may serve as a surrogate measure of collapsibility. The present work aimed to compare the predictive use of CPAP level compared to detailed physiologic measures of collapsibility. METHODS: Therapeutic CPAP levels and gold-standard pharyngeal collapsibility measures (P(crit) and V(passive)) were retrospectively analysed from a randomised controlled trial (N=20) comparing the combination of oxygen and eszopiclone (treatment) versus placebo/air control. Responders (9/20) to treatment were defined as those who exhibited a 50% reduction in AHI plus an AHI<15 events per hour on-therapy. RESULTS: Responders to treatment had a lower therapeutic CPAP requirement compared to non-responders (6.6 [5.4 – 8.1] vs 8.9 [8.4 – 10.4] cmH(2)O, p=0.007), consistent with their reduced collapsibility (lower P(crit), p=0.017, higher V(passive) p=0.025). Therapeutic CPAP level provided the highest predictive accuracy for differentiating responders from non-responders (AUC=0.86±0.9, 95%CI: 0.68–1.00, p=0.007). However, P(crit) (AUC=0.83±0.11, 95%CI: 0.62–1.00, p=0.017) and V(passive) (AUC=0.77±0.12, 95% CI: 0.53–1.00, p=0.44) both performed well, and the difference in area under the curve (AUC) for these 3 metrics was not statistically different. A therapeutic CPAP level ≤ 8cmH(2)O provided 78% sensitivity and 82% specificity (positive predictive value =78%, negative predictive value=82%) for a response to these therapies. CONCLUSION: Therapeutic CPAP requirement, as a surrogate measure of pharyngeal collapsibility, predicts the response to non-anatomical therapy (oxygen and eszopiclone) for OSA.